Conformational Fixation of a Rectangular Antiaromatic [28]Hexaphyrin Using Rationally Installed Peripheral Straps. Issue 13 (17th February 2016) - Yoneda, Tomoki; Kim, Taeyeon; Soya, Takanori; Neya, Saburo; Oh, Juwon; Kim, Dongho; Osuka, Atsuhiro
Abstract: A rectangular [28]hexaphyrin bearing outer straps at the long side has been synthesized by SN Ar reaction of [26]hexaphyrin with allyl alcohol, intramolecular olefin metathesis by using Hoveyda–Grubbs second‐generation catalyst, and reduction with NaBH4 . The peripheral straps enforce a rectangular conformation for the [28]hexaphyrin, which shows Hückel antiaromatic character, as confirmed by its planar X‐ray structure, a strong paratropic ring current, characteristic UV/Vis/NIR absorption features, small electrochemical HOMO–LUMO gap, and very fast S1 decay. Abstract : A [28]hexaphyrin bearing rationally installed peripheral straps at the long side has been synthesized. The straps suppress the molecular twist into a Möbius conformer, enforcing the rectangular conformation and Hückel antiaromatic character as probed by its X‐ray structure, a strong paratropic ring current, characteristic UV/Vis/NIR absorption features, small electrochemical HOMO–LUMO gap, and very fast S1 ‐decay.